Ngaji Tarekat Sebagai Sarana Penanaman Nilai-nilai Keagamaan: Studi Fenomenologis Pada Masyarakat Dukuh Bojonganlor desa Prapaglor - Hanandita Dewi Marselinda; Benny Kurniawan (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
This study aims to reveal the meaning and value of religious education in "Ngaji Tarekat" and the significant changes in religious character experienced by the people of Dukuh Bojonganlor, Prapaglor Village. This study is a qualitative study with a phenomenological approach. The subjects in this study were teachers and congregations of the Qadiriyah Naqsyabandiyah (TQN) Tarekat Majelis Ta'lim Al-Ikhlas. Data collection techniques were through observation, interviews, and documentation. Data analysis used were data collection, data reduction, data presentation, as well as drawing conclusions and verification. The results of the study indicate that tarekat recitation plays an important role in spiritual and moral development. Through dhikr, wirid, and the guidance of the mursyid, the congregation gains inner peace, increases in worship, and the formation of monotheism, tazkiyah al-nafs, noble morals, and discipline in worship. Real changes are also seen in their religious character, namely becoming more devout in worship, polite, and balanced between worldly and hereafter life.